The effect of Health System Reform Plan on health indicators in population covered by Ahvaz University of Medical Science - Simin Shams Javi; Pouran Raeissi; Amir Ashkan NasiriPour (Tehran University of Medical Sciences, 2020)
Background: One of the fundamental changes in the health system of Iran in recent years is the "health system reform plan", that the effects of which should be examined from various dimensions. The purpose of this study is to determining the effect of health system reform plan on health indicators in population covered by Ahvaz University of Medical Sciences.   Materials & Methods: In this descriptive-analytical study, the data of the selected health indicators of Ahvaz University of Medical Sciences in the period before and after the health care system reform plan (from 2012 to 2018) was collected, described and analyzed with SPSS.   Results: The highest rate of change in mortality indices was between 2013 and 2015, orderly in U5MR, IMR & NMR, With the mean difference 13.282, 10.825 & 7.955 (P=0.001, P=0.002 & P=0.004). The highest rate of change in Care Coverage for Children Under-five, is between 2014 and 2015 with mean difference of 11.335 and about the Antenatal Care Coverage, between 2014 and 2017, with mean difference 10.050 (orderly p=0.002 & p>0.001). MMR was not significant.   Conclusion: The time trend analysis on health indicators confirms that the changes in the early years of the reform plan have been a lot, then it has slow down. Most of the change in health indicators is related to years of 2015 and 2016. The findings indicate that the latest health reform plan in Iran has improved the mortality indices (Reduce in NMR, IMR & U5MR), Care Coverage for Children Under-five and Antenatal Care Coverage (6+). Health reform plan has not affected on MMR.